2001
DOI: 10.1590/s0103-50532001000600018
|View full text |Cite
|
Sign up to set email alerts
|

River Sediment Analysis by Slurry Sampling FAAS: Determination of Copper, Zinc and Lead

Abstract: Foi desenvolvido um procedimento experimental para a análise direta de sedimento. Com o emprego deste procedimento, foram determinados cobre, zinco e chumbo, e foram conseguidas recuperações quantitativas para esses metais com baixo custo e manipulação mínima das amostras. Foram investigadas a influência da concentração do ácido nítrico no preparo da suspensão, bem como o tamanho de partícula do sedimento. As suspensões do sedimento foram tratadas com ácido nítrico 6,0 mol L -1 e cloreto de amônio 2% (m/v), e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Slurry sampling methods using flame AAS (FAAS) are described less frequently in the literature (Alves, Cadore, Jardim, & Arruda, 2001;DeAlmeida, Leandro, DaCosta, Santelli, & DelaGuardia, 1997;Pereira, Berndt, & Arruda, 2002;Quaresma, Cassella, & De LaGuardia, 2004;Santos et al, in press), at least in part because of the limited sensitivity of this technique, and the risk of clogging the nebulizer capillary with sample particles.…”
Section: Introductionmentioning
confidence: 99%
“…Slurry sampling methods using flame AAS (FAAS) are described less frequently in the literature (Alves, Cadore, Jardim, & Arruda, 2001;DeAlmeida, Leandro, DaCosta, Santelli, & DelaGuardia, 1997;Pereira, Berndt, & Arruda, 2002;Quaresma, Cassella, & De LaGuardia, 2004;Santos et al, in press), at least in part because of the limited sensitivity of this technique, and the risk of clogging the nebulizer capillary with sample particles.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, calibration models for ETV-ICP techniques generally involve aqueous standards as described by de LoosVollebregt and coworkers in a recent comprehensive review article (11). The application of this calibration method for FAAS and ICP techniques can be easily employed but depends on several factors as described in the literature (45).…”
Section: External Calibration With Aqueous Standardsmentioning
confidence: 99%
“…18 The quantification of trace elements in food samples can be performed using the flame atomic absorption spectrometry (F AAS) due to its low cost, simplicity and high analytical throughput, with samples digested by mineral acids (such as HNO 3 , H 2 SO 4 , HClO 4 , HCl) under heating. [18][19][20][21] In spite of the number of studies concerning FA and trace element determinations in pequi fruit found in the literature (mentioned above), only a few studies have been devoted to the quantitative analysis of pequi oil. Within this context, the aim of the present work was to demonstrate the potential of CZE for FFA (palmitic, oleic and linoleic acids) determination in pequi oil samples using ethanolic extraction as a simple sample preparation, and to quantify the trace element levels (Cu, Fe, Mn and Zn) in these samples using F AAS, following a new acid digestion procedure.…”
Section: Introductionmentioning
confidence: 99%